Determinants of Corruption In Indonesia: The Moderating Role of ICT - Syafrul Antoni; Sri Rahayu; Rita friyani; Wira Lestari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the determinants of corruption in Indonesian provincial governments and investigates the moderating role of information and communication technology (ICT). Specifically, the study analyzes the effects of e-government implementation, local government size, and fiscal dependence on corruption levels. The analysis employs panel data from 31 provincial governments in Indonesia during the period 2019–2023, resulting in 155 observations. A Fixed Effect Model (FEM) is applied to estimate the relationships among the variables. The empirical results indicate that e-government implementation does not significantly reduce corruption, suggesting that digitalization alone is insufficient to improve governance outcomes without strong institutional capacity and effective monitoring mechanisms. In contrast, local government size and fiscal dependence on central government transfers show a significant negative relationship with corruption levels. These findings imply that stronger bureaucratic capacity and stricter fiscal supervision mechanisms may contribute to reducing corruption risks. Furthermore, the moderation analysis reveals that ICT does not strengthen the relationship between e-government and corruption reduction. However, ICT significantly moderates the relationship between government size and corruption, indicating that technological development may increase governance complexity within larger bureaucratic structures when digital governance systems are not optimally implemented. Overall, the findings highlight that digital technology is not a standalone solution for combating corruption. Its effectiveness depends largely on institutional quality, governance capacity, and robust accountability mechanisms.